Exact stochastic analysis of coupled bending–torsion beams with in-span supports and masses. (October 2018) - Burlon, Andrea; Failla, Giuseppe; Arena, Felice
Abstract: The stochastic response of a coupled bending–torsion beam, carrying an arbitrary number of supports/masses, is investigated. Using the theory of generalized functions in conjunction with the Euler–St. Venant coupled bending–torsion beam theory, exact analytical solutions under stationary inputs are obtained based on frequency response functions derived by two different closed-form expressions. The analytical solutions are obtained for all response variables, considering any number of supports/masses along the beam and arbitrary spatial load distributions. Two numerical examples are reported.